BABILANGAN: THE TRADITION OF BANJARESE PEOPLE BEFORE MARRIAGE IN FIQH MUWAZANAH PERSPECTIVE - Wafi, Akhmad; Muzainah, Gusti; Siti Maghfirah; Nur Hikmah (Fakultas Syariah UIN Antasari, 2025)
The custom of